Реологічні властивості крохмально-каолінових систем - Ткачук, Г. С.; Щербань, В. Ю. (Eastern-European Journal of Enterprise Technologies, 2009)
Starch-kaolin suspensions properties were resumed in purpose to research a possibility of using as cotton warps size additives hydrophilic aluminium compounds. Using these substances adhesion to yarn and technological indexes of weaving increase owing to hygroscopic and plastic size films properties